The Use of New Control Card for Health Education about Chemotherapy Procedures for Patients - Tumini, Tumini (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
In every stage of long and complex chemotherapy procedure, of course, it could confuse patients. The purpose of this queasy experimental research was to analyze the effect of education from nurses about chemotherapy procedure on patients knowledge level toward the use of new card at one-stop oncology poly (POSA (Poli Onkologi Satu Atap)) of Dr. Soetomo Hospital, Surabaya, by using